GARBAGE RECYCLING TO RUPIAH IN SUMBERDODOL, PANEKAN-MAGETAN - Suyanto; Sri Warjiyati; Nur Fadilah; Kholilah Ulfa (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2022)
Garbage is an unused and must be removed, it is produced by human activities originating in industrial, mining, agricultural, agricultural, fisheries, transportation, domestic, commercial, and other human activities. Garbage Banks are one of the innovative creations to harness the economic value contained in garbage done by society and indirectly reduce the amount of garbage. The study focused on (1) how people's empowerment through garbage Banks, (2) factors affecting public empowerment through garbage Banks (3) the goal of creating trash Banks that would later be expected to improve the skills and insights of the public public utilities. Pankean Magazine for the disposal of garbage and for economic benefits, and for creating a clean environment. The research method employed is a qualitative descriptive study method. The result of this activity was the formation of a trash bank organization with the name "title of asri" (a clean receipt bracelet) in the village of sumberbodol.